Los límites de la ciudad : reconocer el espacio urbano mediante el arte contemporáneo - Negre Busó, Marta (2018)
“Bòlit_Residents” is a project that was developed at Carles Rahola high school in 2012, focusing on the topic of “Cities and their peripheries.» The project aimed to trigger crea¬tivity, sensibility and critical thinking among 12-year-old students, and to motivate them to work within contemporary art